SPL variability management, cardinality and types: an MDA approach. (1st January 2012) - Cabello Espinosa, María Eugenia; Ramos Salavert, Isidro; Gutiérrez Pulido, Jorge Rafael; Gómez Llana, Abel; Limón Cordero, Rogelio
This paper presents a baseline-oriented modelling (BOM) approach to develop families of software products. BOM is a generic solution implemented as a framework that automatically generates software applications using executable architectural models by means of software product line (SPL) techniques. In order to cope with the variability problem, BOM considers its cardinality and type and implements two solutions: the BOM-EAGER and the BOM-LAZY approaches. BOM has been designed following the model-driven architecture (MDA) standard: all the SPL software artefacts are models, and model transformations enact the SPL production plan.